2010
DOI: 10.5694/j.1326-5377.2010.tb03931.x
|View full text |Cite
|
Sign up to set email alerts
|

Is psychological distress in people living with cancer related to the fact of diagnosis, current treatment or level of disability? Findings from a large Australian study

Abstract: Objective: To investigate whether the observed elevated levels of psychological distress in cancer survivors relate specifically to aspects of cancer diagnosis, to treatment or to disability. Design, participants and setting: Self‐reported questionnaire data on demographic, health and lifestyle factors and mental health from 89 574 Australian men and women aged 45 years or older, sampled from the Medicare database for the 45 and Up Study from 1 February 2006 to 30 April 2008. Logistic regression was used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 21 publications
(25 reference statements)
7
55
2
1
Order By: Relevance
“…33 K10 has been used in this binary manner, with 22 as the cut-point, in the previously published analyses of the 45 and Up Study. [34][35][36] Other individual-level measures Social interactions were measured using four questions from the shortened version of the Duke Social Support Index. 37 Three of the questions asked a number of times over the past week were whether or not a participant (i) spent time with friends or family they did not live with; (ii) talked to someone (friends, relatives or others) on the telephone and (iii) attended meetings at social clubs or religious groups.…”
Section: Psychological Distressmentioning
confidence: 99%
“…33 K10 has been used in this binary manner, with 22 as the cut-point, in the previously published analyses of the 45 and Up Study. [34][35][36] Other individual-level measures Social interactions were measured using four questions from the shortened version of the Duke Social Support Index. 37 Three of the questions asked a number of times over the past week were whether or not a participant (i) spent time with friends or family they did not live with; (ii) talked to someone (friends, relatives or others) on the telephone and (iii) attended meetings at social clubs or religious groups.…”
Section: Psychological Distressmentioning
confidence: 99%
“…11,12 Among cancer survivors, poor physical quality of life is reported more frequently than poor mental quality of life, 12 and patient distress is strongly related to impaired physical functioning. 11 Rehabilitation programs may serve to improve functional capacity lost as a result of cancer etiology and treatment. Early intervention through participation in comprehensive rehabilitation therapies across the care continuum may be effective in restoring functional deficits and preventing long-term disability related to cancer.…”
mentioning
confidence: 99%
“…Previous studies have shown similar mediation by PFL in the association between psychological distress and other disease outcomes, such as heart disease, arthritis and cancer 26 27. The excess risk of psychological distress attributable to disability is about 40 times greater on average than that attributable to cancer diagnosis, in the absence of disability, among long-term cancer survivors 26.…”
Section: Discussionmentioning
confidence: 83%
“…The excess risk of psychological distress attributable to disability is about 40 times greater on average than that attributable to cancer diagnosis, in the absence of disability, among long-term cancer survivors 26. Further, the risk of depression in those with arthritis or heart disease was shown to attenuate when activities of daily living and instrumental activities of daily living limitation were considered, demonstrating that physical limitation mediates, to some extent, the association between depression and these conditions 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation